On the recent slowdown in productivity growth in advanced economies - Herbert Giersch; Frank Wolter (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
After two and a half decades of prosperous postwar development, western industrialised countries recently experienced a slowdown of economic growth and productivity advance together with an increase in the rates of inflation and unemployment. The deep recession of 1974/75 has uncovered fundamental structural weaknesses; since then, the advanced economies have not regained the momentum of the 1960s. In this paper, we shall attempt to contribute to a better understanding of this malaise. But as our comparative advantage is not in growth-accounting and as we do not believe that we can single out one or two specific causes, we shall merely aim at forming an idea (perhaps only a rather vague one) which might be further developed into a paradigm or research programme (in Lakatos' sense).
Keywords: 330